The effects of increasing dietary lysine in the phase III starter diet on growth performance of segregated early-weaned pigs - Owen, K.Q.; Bergstrom, J.R.; Friesen, K.G.; Smith, J.W. II; Richert, B.T.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred forty-four high-health, high-lean growth barrows were used to determine the dietary lysine requirement to maximize growth performance from 40 to 75 lb. The experiment was designed as a randomized complete block, with blocks established on initial weight. Prior to the start of the study, pigs were fed a common Phase II diet (1.4% lysine) for 14 d. After the 14 d acclimation period, pigs were allotted to each of six dietary treatments, ranging from .75 to 1.25% digestible lysine (.91 to 1.49% total dietary lysine). Pigs were housed in pens of four, with six replicate pens per treatment. Pig weights and feed disappearance were measured on d 7, 14, and 21 of the experiment to calculate average daily gain (ADG), average daily feed intake (ADFI) , and feed efficiency (F/G). Average daily gain increased with increasing dietary lysine from 40 to 75 lb, with a maximum observed at approximately 1.25 to 1.37% total lysine. Average daily feed intake from 40 to 75 lb was not influenced by dietary lysine. Increasing dietary lysine resulted in improved F/G, with pigs fed between 1.25 and 1.37% lysine having the best F/G. Based on the feed intake observed in this study, high-lean growth barrows that have been segregated early-weaned to improve health status require at least 16 to 17 gld of lysine from 40 to 75 lb to maximize ADG and F/G. These requirements for the Phase III starter diet are substantially higher than previously recommended.
Keywords: Swine; Pigs; Growth; Genotype; Lysine